Trajectory tracking sliding mode control for cart and pole system - Nguyen, Minh Tam; Huynh, Xuan Dung; Nguyen, Phong Luu; Le, Thi Thanh Hoang; Hong , Gia Bao; Nguyen, Van Dong Hai; Truong , Thanh Liem; Mircea Nitulescu; Ionel Cristian Vladu (Journal of Technical Education Science, 2019)
Cart and Pole is a classical model in the control laboratories for testing control algorithm. Balancing control at equilibrium the point has been operated many times on this model with various methods. However, a control algorithm that makes system to track a suggested trajectory, when stability requirement is guaranteed by mathematics, is still opened. In this paper, the authors suggest using a sliding mode control – a nonlinear algorithm- to stabilize cart and pole system at an equilibrium point. Then, this algorithm controls the cart to track the trajectory of sine signal and pulse signal when still stabilizing pendulum on inverted position. Sliding Mode Control method is familiar in control and automation. In this paper, the abilities of Sliding Mode Control are shown its abilities in both simulation and experiment results. On Matlab/Simulink simulation, Sliding Mode Control proves its advantages over LQR control. Then, experiments show the results of applying a sliding control for real model .